Forensic investigation of aliphatic hydrocarbons in the sediments from selected mangrove ecosystems in the west coast of Peninsular Malaysia - Vaezzadeh, V.; Zakaria, M.P.; Shau-Hwai, A.T.; Ibrahim, Z.Z.; Mustafa, S.; Abootalebi-Jahromi, F.; Masood, N.; Magam, S.M.; Alkhadher, S.A.A. (Elsevier, 2015)
Peninsular Malaysia has gone through fast development during recent decades resulting in the release of large amounts of petroleum and its products into the environment. Aliphatic hydrocarbons are one of the major components of petroleum. Surface sediment samples were collected from five rivers along the west coast of Peninsular Malaysia and analyzed for aliphatic hydrocarbons. The total concentrations of C10 to C36 n-alkanes ranged from 27,945 to 254,463 ng·g- 1dry weight (dw). Evaluation of various n-alkane indices such as carbon preference index (CPI; 0.35 to 3.10) and average chain length (ACL; 26.74 to 29.23) of C25 to C33 n-alkanes indicated a predominance of petrogenic source n-alkanes in the lower parts of the Rivers, while biogenic origin n-alkanes from vascular plants are more predominant in the upper parts, especially in less polluted areas. Petrogenic sources of n-alkanes are predominantly heavy and degraded oil versus fresh oil inputs.